Critical-feminist studies of funerals: A way to grasp the rite’s complexity - Jarnkvist, Karin (Approaching Religion, 2023)
This article aims to show how critical-feminist studies can improve research on funerals by contributing to a more complex understanding of ritualization and how it can be explored. The article discusses central issues within critical-feminist theory in relation to previous studies of funerals in Sweden and presents theoretical approaches that may improve the field of funeral studies. Intersectionality, queer phenomenology and ritual practice theory are introduced as examples of approaches that might help the researcher deal with questions of representation in research, rejection of othering and application of non-essentialism – central issues in critical-feminist theory. Critical-feminist studies may, for example, uncover intersections of power relations in the ritual field, reveal experiences of inclusion/exclusion and contribute to a relational and dynamic understanding of ritual practice. Thereby, they provide complex knowledge of funerals, essential for understanding their functions for individuals and societies in times of ritual change.